Application of Microsoft Teams Applications in History Learning - Tanikwele, Mevi Bozed; Sarkadi; Ibrahim, Nurzengky (LPPM Undiksha, 2023)
The Microsoft Teams application is one of the learning applications that can be applied to online distance learning during the covid-19 pandemic, with the application of the Microsoft Teams learning application, teachers can increase students' interest/motivation in learning while they are at home. This study aims to analyze the implementation of history learning, the application of the Microsoft Teams application, and the obstacles encountered by history teachers using the Microsoft Teams application in learning history. This type of research uses qualitative research with a case study approach. The subjects in this study were 1 history teacher and 5 students in class XII IPS 5 whose learning was done through the Microsoft Teams application. The trial of this research was in class XII IPS 5 with 35 students. Data collection methods used interviews, observations and take notes. Analysis of the data used is the Analysis Interactive model of Miles and Huberman. The results showed that learning history during distance learning using the Microsoft Teams application can still run smoothly, but this condition can also affect the interaction of teachers and students in learning. The teacher has been able to apply the Microsoft Teams application in learning because there are media that support the teacher during online learning, the learning media in question are the meter, quiz, padlet and group room. The obstacles encountered by the teacher in learning history by implementing the Microsoft Teams application were mainly on the internet network so that students were quite passive in carrying out history learning.